Radiation and Checkpoint Inhibitor Immunotherapy Lead to Long Term Disease Control in a Metastatic RCC patient With Brain Metastases - Levitin, Maria; Ofori, Joel; Shin, Woo Jae; Huang, Jiayi; Daly, Mackenzie; Cao, Dengfeng; Pachynski, Russell (Frontiers in Oncology, 2020)
Renal cell carcinoma (RCC) comprises 4.2% of all new cancer cases in the United States and 30% of cases are metastatic (mRCC) at diagnosis. Brain metastatic RCC historically has poor prognosis, but the development of immune checkpoint inhibitors has revolutionized their care and may be successfully combined with SBRT to improve prognosis. Here, we present a case of a patient with mRCC who had brain metastases treated with concurrent immune checkpoint inhibitors and SBRT. He continues to survive with good functional status years following his initial diagnosis. We discuss the relevant history regarding treatment approach in patients with brain metastatic RCC, ongoing trials focusing on the combination of immunotherapy and radiation, and the potential and promise of the abscopal effect.